2023
DOI: 10.1021/acs.inorgchem.2c03573
|View full text |Cite
|
Sign up to set email alerts
|

Radiochemical, Computational, and Spectroscopic Evaluation of High-Denticity Desferrioxamine Derivatives DFO2 and DFO2p toward an Ideal Zirconium-89 Chelate Platform

Abstract: Desferrioxamine (DFO) has long been considered the gold standard chelator for incorporating [89Zr]Zr4+ in radiopharmaceuticals for positron emission tomography (PET) imaging. To improve the stability of DFO with zirconium-89 and to expand its coordination sphere to enable binding of large therapeutic radiometals, we have synthesized the highest denticity DFO derivatives to date: dodecadentate DFO2 and DFO2p. In this study, we describe the synthesis and characterization of a novel DFO-based chelator, DFO2p, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 87 publications
0
7
0
Order By: Relevance
“…Previous zirconium-89 chelation and radiochemical stability data reported from the chelators DFO-Em, DFO2, and DFO2p have shown that increasing the coordination number from what DFO offers (max CN = 6) to saturate the coordination sphere of [ 89 Zr]­Zr 4+ improved the stability of the complexes. The glutamic acid linker used in DFO-Em also greatly improved water solubility relative to DFO .…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…Previous zirconium-89 chelation and radiochemical stability data reported from the chelators DFO-Em, DFO2, and DFO2p have shown that increasing the coordination number from what DFO offers (max CN = 6) to saturate the coordination sphere of [ 89 Zr]­Zr 4+ improved the stability of the complexes. The glutamic acid linker used in DFO-Em also greatly improved water solubility relative to DFO .…”
Section: Resultsmentioning
confidence: 94%
“…To assess whether Zr-(DFO-Km) can attain this preferred cis–cis–trans–trans octadentate Zr­(IV) coordination geometry, we performed DFT calculation using Materials Studio (DMOL3) to determine the energy of 16 possible geometric isomers (Λ-enantiomers) of Zr-(DFO-Km) (Figures and ) using similar methods as previously published. ,,, All calculations contained identical molecular formulas and the same number of atoms, and were calculated with water as solvent (COSMO). As with our DFT study of Zr-(DFO-Em), the large size and flexibility of Zr-(DFO-Km) makes it difficult to settle on a single most stable confirmation of each isomer.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations